The L2, 1-norm-based unsupervised optimal feature selection with applications to action recognition. (December 2016) - Wen, Jiajun; Lai, Zhihui; Zhan, Yinwei; Cui, Jinrong
Abstract: This paper proposes a matrix-based feature selection and classification method that takes the advantage of L 2, 1 -norm regularization. Current studies show that feature extraction and selection have been important steps in classification. However, the existing methods consider feature extraction and selection to be separated phases, which generates suboptimal features for the recognition task. Aiming at making up for this deficiency, we designed a novel classification framework that performs unsupervised optimal feature selection (UOFS) to simultaneously integrate dimensionality reduction, sparse representation, jointly sparse feature extraction and feature selection as well as classification into a unified optimization objective. Specifically, an L 2, 1 -norm-based sparse representation model is constructed as an initial prototype of the proposed method. Then a projection matrix with L 2, 1 -norm regularization is introduced into the model for subspace learning and jointly sparse feature extraction and selection. Finally, we impose a scatter matrix-like constraint on the proposed model in pursuit of the features with less redundancy for recognition. We also provide an alternative iteration optimization with convergence analysis for solving UOFS. Experiments on public gesture and human action datasets validate the superiority of UOFS over other state-of-the-art methods. Highlights: A feature selection and classification model is proposed. Adjacency graph and projection matrix are simultaneously optimized in our model. The model can conduct jointly sparse feature extraction and feature selection. The high correlation lying in the video frames is reduced in our model. An efficiency algorithm with convergence proof is provided to solve the model.